Pemerolehan Fonologi Bahasa Indonesia Anak Laki-Laki Usia 4 (Empat) Tahun - Riri Amanda Fitriana (Ridwan Institute, 2021)
This study aims to describe the acquisition of phonology in the form of acquisition of vowels, consonants, and diphthongs. The method in this research is a qualitative method with a case study approach obtained by a 4 year old man. In this study it was found that the IHA had acquired complete vowel phonemes at the age of 4 years and most consonant had also been obtained. He has also mastered the sound of double vowels or diphthongs. While the fricative sound [f], the vibrating sound [r] was not mastered until the age of 4 years. Uniquely, IHA has its own ola if it finds consonant / l / and consonant / r / which is located at the end of a word. IHA will replace it with the phoneme // Å‹ //. This happens because the speech motor that IHA has is incomplete or not yet fully developed.